Nursing Care for Patients with Peripherally Inserted Central Catheters (PICC) - Sanguanphan, Nichawadee (Siriraj Medical Bulletin, 2025)
The peripherally inserted central catheter (PICC) is an essential medical device widely used in the treatment of patients requiring long-term intravenous therapy, such as chemotherapy, prolonged antibiotic administration, and total parenteral nutrition. PICC placement reduces the burden of repeated venipuncture, enhances patient comfort, and supports the effectiveness of treatment. Despite its benefits, the use of PICC lines carries potential risks, including catheter occlusion, dislodgement, and catheter-related infections. Consequently, nursing care plays a pivotal role in ensuring safe and effective management of patients with PICCs. Comprehensive nursing responsibilities include pre-insertion assessment of patient suitability, preparation for catheter placement, and strict adherence to aseptic techniques during all procedures. Post-insertion care focuses on appropriate flushing and locking methods to maintain catheter patency, regular monitoring of the insertion site for signs of infection or complications, and proper dressing changes following sterile protocols. Furthermore, patient and family education is fundamental to safe self-care at home. This includes maintaining catheter hygiene, recognizing early warning signs such as fever, pain, redness, or discharge, and adhering strictly to follow-up appointments and medical recommendations. Effective nursing practice requires a combination of knowledge, technical skills, and compliance with evidence-based standards. By integrating these practices, nurses not only help reduce complication rates but also improve the quality of care and patient safety. Moreover, empowering patients and families with knowledge and self-care strategies promotes treatment adherence and enhances overall quality of life. Ultimately, systematic and holistic nursing management of PICC lines contributes significantly to successful treatment outcomes and patient well-being.